Biological Aspect of Dates Supplementation in Lactating Rats’ Diet - Nahla Elbostany; Fathia M. Soliman; Maha Mahmoud; Ali I.S. Ahmed (Journal of High Institute of Public Health, 2007)
In the current study on lactation in rats’ dates (D) ratio in diet was examined in supporting this physiological case. Dates were used both at 25 or 50% with another food sources such as skimmed milk (SM) at 10 or 30% plus a source for CHO such as sweet potatoes (SP) at a variable ratio of 10, 25, or 35%. A special herbal mixture of extract as additives (AD) was added to all groups except the NC. The NC control composition was 46% both SM and corn starch (S), wherein the ratio of proteins in diet, almost 17.5%, was corrected using 10 or 20% of a plant-rich protein antioxidant semimodified food (AC). Date has been found to be preferable up to 25% in a special combination as lactating diet. The food component of the best diet under the condition of this experiment, i.e., the diet met the most healthy both mothers and infants, were the skimmed milk (SM) of 10% plus sweet potatoes (SP) at a high ratio of 25%. It seems that little higher ratio of proteins, i.e., 18%, most of which are plants with plenty amount of vegetable CHO and less than 10% fat in oily form with an adequate amount of minerals and vitamins, particularly found in D and SP, are important food toleration for those rats. This is formally seen in pregnancy. Fortunately, the diet of choice according to the above mentioned role gave also the optimal BW measurement. However, rapid weight loss through diet or medication should not be attempted during lactation. Under the light of blood cell counts, blood analysis and both liver and kidney histopathology, the special extract used seemed to be important as source for some minor elements. The conjugation of those micronutreints and the macronutreints provided by the food system mentioned above has strongly supported that sort physiological nutritional requirements. Lactation is a special physiological case with a specific metabolic hormonal balance. This is an adapted hormonal shift (HS) follows this particular physiological status. It is such a hormonal program that strongly connected to feeding category. The present data show an alternative food combination that support mother health based on biological evaluation used, i.e., liver function and histology was group 4 of 25 D, 10 AC, 30 SM, and 25 SP. More investigation is needed to observe the role of the food additives used in the presence of main nutrients on this profounded kind of hormonal status.